Preliminary Study about Comparison of Potato Minitubers Production in Conventional Culture and Modern Culture – Aeroponic - Andreea Tican; Carmen Chelmea; Mihaela Cioloca; Monica Popa; Maria Stefan (Journal of Agriculture and Rural Development Studies)
In 2024, within the Research Laboratory for Plant Tissue Cultures, of the National Institute of Research and Development for Potato and Sugar Beet Brașov, the minituberization process was evaluated for four potato varieties (Azaria, Brașovia, Cosiana and Cezarina) by applying two cultivation methods: aeroponic culture (wihout substrate) and classical culture (with a peat-perlite mixture as the cultivation substrate). The varieties studied behaved differently in minituberization, depending on the culture applied. The average number of minitubers (in the two cultivation methods) was between 16.50 (Azaria variety) and 5.17 (Cosiana variety). The statistical analysis (performed to establish the influence of the type of culture) shows the superiority in minituberization process of taeroponic culture (12 minitubers), compared to the classical culture on peat-perlite substrate (6.94).